Substitution and preparation effects on the molecular-scale morphology of PPV films - Kemerink, Martijn; Duren, Jeroen Karolus Johannes van; Breemen, Albert J. J. M. van; Wildeman, J.; Wienk, Martinus Maria; Blom, P. W. M.; Schoo, H. F. M.; Janssen, René A. J. (Macromolecules, 2005)
The morphology of spin-cast films of poly(p-phenylenevinylene) (PPV) derivatives is studied as a function of the substitution pattern of the conjugated backbone. Moreover, the influence of concentration in the casting solution, annealing, the choice of solvent, and the role of defects are addressed. By using a recently developed scanning-probe technique, we are able to visualize individual polymer chains and aggregates on the surface of spin-cast films. We find that a symmetric substitution pattern strongly promotes interchain aggregation in the surface layer, whereas an unsymmetric pattern in some cases leads to intrachain or self-aggregation. The nature of these intrachain aggregates is further investigated using molecular dynamics simulations. The observed molecular morphologies can in most cases be qualitatively related to macroscopic electrooptical properties. Therefore, our results strongly suggest that the surface morphology may be regarded as indicative of the morphology of the entire film.
Gesehen am 16.12.2019